2004
DOI: 10.3171/jns.2004.100.2.0236
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the head-shaking method combined with cisternal irrigation with urokinase in preventing cerebral vasospasm after subarachnoid hemorrhage

Abstract: The head-shaking method significantly reduced the incidence of symptomatic vasospasm, cerebral infarction, and permanent ischemic neurological deficit and improved the clinical outcomes in patients who underwent cisternal irrigation therapy after aneurysmal SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 71 publications
0
48
0
1
Order By: Relevance
“…Currently, there are many kinds of treatments for CVS after SAH [13][14][15][16][17][18][19][20][21]. However, these methods can only reduce a part of occurrence of CVS [22].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are many kinds of treatments for CVS after SAH [13][14][15][16][17][18][19][20][21]. However, these methods can only reduce a part of occurrence of CVS [22].…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6,7,[14][15][16][17] However, the majority of these studies also differed in design, as they compared experimental with no treatment for DCI, included mainly good grade SAH patients, or investigated exclusive cisternal and urokinase application. [3][4][5][6][7] The relation of the type of fibrinolytic agent with outcome remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6,7,[14][15][16][17] However, the majority of these studies also differed in design, as they compared experimental with no treatment for DCI, included mainly good grade SAH patients, or investigated exclusive cisternal and urokinase application. [3][4][5][6][7] The relation of the type of fibrinolytic agent with outcome remains incompletely understood. Despite some animal studies reporting a neurotoxic effect for rt-PA Serious adverse events 0 0 GOS d/c indicates Glasgow Outcome Scale at discharge; GOS 3 months, Glasgow Outcome Scale after 3 months; hydrocephalus, incidence of permanent hydrocephalus requiring ventriculoperitoneal shunt surgery at discharge; new cerebral infarction, cerebral infarction exclusively related to delayed cerebral ischemia; PCT, perfusion computer tomography; PCT VSP, mean transit time values >4.2 s of baseline PCT measurements; rescue therapy, angiographic, intra-arterial nimodipine administration and balloon angioplasty; and VSP, vasospasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of treatment was first described by Suzuki et al in 1990 and later picked up by Kawamoto et al [74,75]. Kawamoto et al reported about a marked reduction of delayed vasospasm, DIND and DCI and an improvement of neurological outcome by continuous head motion combined with cisternal irrigation.…”
Section: Continuous Head Motion and Rotational Therapy For Subarachnomentioning
confidence: 99%